El caso de los buzos miskitos: un laboratorio vivo para auditar la adaptabilidad del Sistema Interamericano de Derechos Humanos - Cabezas Albán, Víctor Daniel (2020)
This paper addresses the level of adaptability of the Inter-American Human Rights System towards different issues, such as the human rights of legal entities and the international responsibility of legal persons for human rights violations. This analysis is made through the lecture and narration of the case Opario Lemoth Morris y otros vs. Honduras, which has been recently summited before the Inter-American Human Rights Court.